Toll-like receptors as a missing link in Notch signaling cascade during neurodevelopment - Stojanovic, Mario; Kalanj-Bognar, Svjetlana (Frontiers in Molecular Neuroscience, 2024)
Neurodevelopment encompasses a complex series of molecular events occuring at defined time points distinguishable by the specific genetic readout and active protein machinery. Due to immense intricacy of intertwined molecular pathways, extracting and describing all the components of a single pathway is a demanding task. In other words, there is always a risk of leaving potential transient molecular partners unnoticed while investigating signaling cascades with core functions—and the very neglected ones could be the turning point in understanding the context and regulation of the signaling events. For example, signaling pathways of Notch and Toll-like receptors (TLRs) have been so far unrelated in the vast body of knowledge about neurodevelopment, however evidence from available literature points to their remarkable overlap in influence on identical molecular processes and reveals their potential functional links. Based on data demonstrating Notch and TLR structural engagement and functions during neurodevelopment, along with our description of novel molecular binding models, here we hypothesize that TLR proteins act as likely crucial components in the Notch signaling cascade. We advocate for the hypothesized role of TLRs in Notch signaling by: elaborating components and features of their pathways; reviewing their effects on fates of neural progenitor cells during neurodevelopment; proposing molecular and functional aspects of the hypothesis, along with venues for testing it. Finally, we discuss substantial indications of environmental influence on the proposed Notch-TLR system and its impact on neurodevelopmental outcomes.